(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
The political party system in India is experiencing a profound transformation, marked by a renewed emphasis on ideology as a key determinant of electoral behavior and party alignment. For decades, Indian politics was shaped by the hegemony of the Indian National Congress, whose centrist and inclusive platform blurred ideological distinctions in favor of pragmatic governance and populist welfare. However, the rise of the Bharatiya Janata Party (BJP) and the growing prominence of regional parties have ushered in a new era of political competition defined increasingly by clear ideological demarcations. This research explores the ways in which ideological narratives—rooted in nationalism, secularism, economic liberalism, and identity politics—have come to shape party strategies, manifestos, and voter behavior. Using a mixed-method approach that integrates quantitative data from the Election Commission of India and CSDS-Lokniti voter surveys with qualitative analysis of party manifestos and public discourse, the study examines elections from 2004 to 2024. The findings reveal a pattern of ideological consolidation, particularly by the BJP, whose sustained electoral success is attributed to its consistent promotion of Hindutva and pro-market economic policies. Meanwhile, the Congress party’s ideological ambiguity and organizational decline have undermined its ability to effectively counter the BJP’s narrative. Regional parties, once focused primarily on caste and linguistic identities, are now engaging more strategically with broader ideological frameworks to maintain relevance in an increasingly polarized environment. The paper argues that Indian democracy is transitioning from a fragmented, coalition-driven model dominated by identity politics to a more ideologically structured party system. This transformation reflects both a shift in voter consciousness and a deliberate reconfiguration of party strategies in response to socio-economic changes and media influence. Ultimately, the study contributes to a deeper understanding of how ideology functions in a non-Western, postcolonial electoral context, challenging the notion that Indian voters are driven solely by clientelism or ethnic loyalties. It also highlights the emerging risks of ideological polarization and majoritarianism, suggesting the need for renewed scholarly and civic engagement with the normative foundations of India’s democratic institutions.